Anticoagulation Duration After First Venous Thromboembolism: Real-Life Data From the International, Observational WHITE Study. (November 2021) - Palareti, Gualtiero; Bignamini, Angelo A.; Cini, Michela; Li, Young-Jun; Urbanek, Tomasz; Madaric, Juraj; Bouslama, Kamel; Sokurenko, German Y.; Andreozzi, Giuseppe M.; Matuška, Jiří; Mansilha, Armando; Barinov, Victor
Background: International guidelines recommend at least three months anticoagulation in all patients after acute venous thromboembolism (VTE) and suggest those with unprovoked events be considered for indefinite anticoagulation if the risk of recurrence is high and the risk of bleeding during treatment non-high. Other authors have recently argued against using a dichotomy unprovoked/provoked events to decide on anticoagulation duration and suggest instead using overall risk factors present in each patient as the basis for deciding. Aim: This sub-analysis of the WHITE study aimed at assessing the reasons for the treatment decisions taken by doctors in different countries. Results: 1240 patients were recruited in 7 countries (China, Czechia, Poland, Portugal, Russia, Slovakia, and Tunisia). Anticoagulation was extended in 51.7% and 49.3% of patients with unprovoked or provoked events (n.s.); stopped in 15.4% versus 28.9% ( P  < .0001), and changed to antithrombotic drugs (sulodexide or aspirin) in 32.9% versus 21.8% ( P  < .0001). In the 430 subjects with isolated distal deep vein thrombosis (IDDVT) anticoagulation was stopped in 34.4%, continued in 37.0% (mainly those with post-thrombotic syndrome [PTS]) and switched to antithrombotics in the balance. High risk of recurrence was the most prevalent reason (>83% of cases) given to continue anticoagulation, regardless of nature and site of the index events, followed by risk of bleeding and presence of PTS signs. Conclusion: On average, attending physicians estimated the risk of recurrence in real life conditions, and the consequent therapeutic decision, using all the information available, not limiting to the location or nature of the index event.